A Double-Layer Patch Design for Local and Controlled Drug Delivery as an Intraoperative Custom-Made Implant-Coating Technology. Issue 2 (April 2016) - Trajkovski, Branko; Petersen, Ansgar; Perka, Carsten; Scharnagl, Nico; Mathew, Simi; Wischke, Christian; Lendlein, Andreas; Duda, Georg N.
Background: The specific biological need of patients frequently becomes obvious just in the intraoperative setting. We hypothesized that a double-layer patch approach that allowed rapid attachment to an implant surface would represent a potential solution for technically challenging intraoperative personalized local drug delivery. Methods: Dexamethasone-loaded poly[( rac -lactide)- co -glycolide] (PLGA) microparticles were embedded within a polyvinyl alcohol (PVA) patch that was attached to metal implant surfaces by in situ polymerization of alkyl-2-cyanoacrylates (CAs). Hydroxyapatite (HA) nanoparticles were also embedded in the PVA patch. Results: Very rapid dexamethasone-release profiles were observed from the PLGA microparticles / PVA patches. The incorporation of HA nanoparticles into the PVA enabled control of CA penetration within the patch, and improved significantly its attachment, while no interference with the drug release was observed. Conclusions: Double-layered patches with 1 layer for drug delivery and 1 as gluing interface could represent a solution for safe and controlled local drug delivery from implant surfaces or other, even biological, materials. The technology platform presented here opens the opportunity for personalized medicine by allowing local administration of drugs with customized release based on an intraoperative application.